The association between oral examination findings and computed tomographic appearance of the equine temporomandibular joint. (25th May 2017) - Carmalt, J. L.; Simhofer, H.; Bienert‐Zeit, A.; Rawlinson, J. E.; Waldner, C. L.
Summary: Background: The temporomandibular joint (TMJ) forms the junction between the maxilla and mandible. Movement of the jaw and resulting masticatory forces have been extensively studied in the horse; however, less is known about the inter‐relationship between this joint and oral and dental pathology. Objectives: To determine the association between specific oral and dental pathologies and anatomical variations of the TMJ imaged with computed tomography (CT) in horses with asymptomatic TMJs. Study design: Retrospective cross‐sectional study. Methods: Horses (n = 201) from three practices with a complete oral examination and skull or upper cervical CT study were reviewed. Age, breed, sex, clinical presentation, oral examination findings, slice width and practice were recorded. Alterations in contour and density of the mandibular condyle, mandibular fossa and intra‐articular disc were also documented. Logistic regression, corrected for clustering by practice, was used to determine whether CT anatomical variations were significantly associated with the oral examination findings. Results: Horses categorised as having abnormal TMJs were older than those with normal TMJ. Horses with periodontal disease were less likely to have abnormal TMJ findings compared with horses with no oral pathology. In contrast, horses with infundibular disease were more likely to have TMJ abnormalities. Main limitations: Due to the cross‐sectional nature of the study, it was difficult to establish whether oral pathology preceded TMJ abnormalities. Conclusions: Despite examining over 200 horses of varying ages, the biological significance of the observed associations between oral, or dental disease and anatomically appreciable temporomandibular joint disorders remains uncertain.